2010
DOI: 10.1021/jm100035c
|View full text |Cite
|
Sign up to set email alerts
|

Design and Syntheses of Permethyl Ningalin B Analogues: Potent Multidrug Resistance (MDR) Reversal Agents of Cancer Cells

Abstract: A series of novel N-arylalkyl-3,4-diaryl-substituted pyrrole-2,5-diones were synthesized. They exhibited promising P-gp modulating activity in a P-gp overexpressing breast cancer cell line (LCC6MDR). Compound 6 (with three methoxy groups at D-ring) displayed the highest P-gp modulating activity. 6 at 1 microM can sensitize LCC6MDR cells toward paclitaxel by 18.2-fold. Interestingly, a synergy on modulating P-gp was noted when 6 and 25 were used together (fractional inhibitory concentration index FICI = 0.42). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 53 publications
3
61
0
Order By: Relevance
“…The amide analogs of 48 enhanced the MDR activity, while amine derivatives (dimers) were inactive as MDR reversal compounds [115]. The synthetic analog of 46, 1-[2-(4-methoxyphenyl)-2-oxoetyl]-3,4-bis(3,4-dimethoxyphenyl)-1H-pyrrole-2,5-dione (52) which was designed from permethyl ningalin B showed a remarkable enhancement of MDR reversal abilities in concentrations up to 1 µM [117,118]. Compound 53, having a methoxy group on the D-ring, showed a 18.2-fold increase in cell sensitization towards paclitaxel at 1 µM concentration, and a 66 fold one when 0.5 µM of 53 was combined with 0.5 µM of 54 [117].…”
Section: Ningalins and Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The amide analogs of 48 enhanced the MDR activity, while amine derivatives (dimers) were inactive as MDR reversal compounds [115]. The synthetic analog of 46, 1-[2-(4-methoxyphenyl)-2-oxoetyl]-3,4-bis(3,4-dimethoxyphenyl)-1H-pyrrole-2,5-dione (52) which was designed from permethyl ningalin B showed a remarkable enhancement of MDR reversal abilities in concentrations up to 1 µM [117,118]. Compound 53, having a methoxy group on the D-ring, showed a 18.2-fold increase in cell sensitization towards paclitaxel at 1 µM concentration, and a 66 fold one when 0.5 µM of 53 was combined with 0.5 µM of 54 [117].…”
Section: Ningalins and Derivativesmentioning
confidence: 99%
“…The synthetic analog of 46, 1-[2-(4-methoxyphenyl)-2-oxoetyl]-3,4-bis(3,4-dimethoxyphenyl)-1H-pyrrole-2,5-dione (52) which was designed from permethyl ningalin B showed a remarkable enhancement of MDR reversal abilities in concentrations up to 1 µM [117,118]. Compound 53, having a methoxy group on the D-ring, showed a 18.2-fold increase in cell sensitization towards paclitaxel at 1 µM concentration, and a 66 fold one when 0.5 µM of 53 was combined with 0.5 µM of 54 [117]. It was found that increasing the number of methoxy groups on ring B of the ningalin scaffold showed only low to moderate P-gp-modulating activity, while the addition of a benzyloxy group on the D ring enhanced the P-gp modulating activity [119].…”
Section: Ningalins and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include methylated quercetin with side chain modifications (compounds 1 and 2 shown in Chart 1) 36 and permethyl ningalin B and its synthetic analogues (compounds 3 and 4 shown in Chart 1). 49,50 They displayed significantly better P-gp modulating activity than the parental compounds. These results suggest that the methylation of polyphenolic compounds is a reasonable and important modification to improve P-gp modulating activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Recent rational modification of polyphenols has provided us promising lead compounds of P-gp inhibitor including flavonoid dimers, quercetin derivatives, curcumin derivatives and methylated ningalin B analogs. 4,[25][26][27][28][29][30][31][32][33] In our previous structureactivity relationship study of methylated ningalin B analogs, two potent hit compounds 1 and 2 ( Fig. 1) were found to be effective P-gp-specific inhibitor.…”
Section: Introductionmentioning
confidence: 99%